Writing abstracts for research articles: towards a framework for move structure of abstracts - Ho, Yoong Wei; Razali, Abu Bakar; Abd Samad, Arshad (Sciedu Press, 2022)
The abstract as a sub-genre of the research article has been explored in many studies, particularly with regards to its rhetorical move structure. However, these studies have mainly focused on the macro-structures of abstracts in terms of the main moves present based on pre-existing models by Swales (1990), Dos Santos (1996), and Hyland (2000). Studies analyzing the micro-structures of abstracts in which the sub-categories under each main category are lacking. This study identifies the main moves of abstracts, the steps and sub-steps within each move to propose a comprehensive framework for abstract structure. Using a move based analysis, 100 research article abstracts in the field of social science and humanities were analyzed at the sentence level, where each sentence was coded and assigned a move. Based on the analysis, five main moves consisting of 12 steps and 25 sub-steps were identified. The frequency of occurrence revealed that Move 2: Introducing Study and Move 4: Presenting Findings were conventional, while Move 1: Situating Research, Move 3: Describing Methodology, and Move 5: Describing Implication and Recommendation were optional. This study has implications for research on the genre analysis of abstracts as well as the teaching of abstract structure in the academic setting.